1989
DOI: 10.1093/oxfordjournals.ejo.a035996
|View full text |Cite
|
Sign up to set email alerts
|

Age and skeletal type-related changes of some cephalometric parameters in Finnish girls

Abstract: The aim of the present study was to define some cephalometric standards in a group of 217 Finnish girls from 7.0 to 18.0 years of age and furthermore to estimate the influence of the skeletal classes on these standards. Age-related changes were seen between the standards of the youngest (7.0-9.5 years) and the oldest (14.5-18.0 years) group where 9 out of 15 of the inspected angles increased with age, three of them ANPr***, SNPg** and SNB* significantly, and 6 decreased, four of them significantly: ANPg***, AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…In a smaller number of North American subjects, the WITS appraisal was found to be skewed in the class III direction, btit the ANB angle showed no definitive trend (21). In a study of 217 Finnish girls, the proportion for class I defined by an ANB value of 0-4° has been reported to be 64%, for class II 27%, and for class III 9% (22). This study also showed a larger proportion of cases in skeletal class III than in dental class III.…”
Section: Discussionmentioning
confidence: 46%
“…In a smaller number of North American subjects, the WITS appraisal was found to be skewed in the class III direction, btit the ANB angle showed no definitive trend (21). In a study of 217 Finnish girls, the proportion for class I defined by an ANB value of 0-4° has been reported to be 64%, for class II 27%, and for class III 9% (22). This study also showed a larger proportion of cases in skeletal class III than in dental class III.…”
Section: Discussionmentioning
confidence: 46%
“…The cranial base angles (n-s-ba, n-s-ar) in group I have been reported to be the same or larger than in group I1 ( I I); our results show that these angles do not differ significantly ( 11). Moreover, the cranial bases in both groups were similar to or a little smaller than those in normal Finnish, Swedish -Pierre Robin svndrome -Pierre Robin syndrome ---Isolated cleft palate I I and Danish populations (10,24,26). During the follow up period the cranial base angles in both groups either remained unchanged or slightly decreased.…”
Section: "-4"mentioning
confidence: 75%
“…Orthodontists are interested in finding answers to the magnitude of change which occurs in the size of facial bones with age, if the changes in mandibular dimensions accompanied by corresponding change in the relationship of the maxilla to the cranial base and if there is a clinically significant circumpubertal acceleration/deceleration in both maxillary and mandibular size (19)(20)(21)(22). They Scammon et al described the remaining growth between the ages of 10 and 20 years as 4% in the cranium and 35% in the middle and upper parts of the face (23).…”
Section: Discussionmentioning
confidence: 99%
“…The changes in craniofacial parameters was studied for several populations in previous studies (14,(19)(20)(21)25,27,28) by using different criteria in selection of subjects, e.g "normal occlusion" (29-32), "acceptable occlusion" (19,20,33,34) and "Angle Class I with no facial deformity" (21,22 (13,14), it has not been studied for the population with dental flourosis yet. Thus we chose our study sample also from Class I individuals having normal occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation